2007
DOI: 10.1055/s-2006-945146
|View full text |Cite
|
Sign up to set email alerts
|

Esophagitis dissecans superficialis associated with bisphosphonates

Abstract: Esophageal injury has been associated with various medications. Here we de− scribe a case of esophagitis dissecans su− perficialis associated with bisphospho− nates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 2 publications
1
16
0
5
Order By: Relevance
“…[18][19][20] Interestingly, one of the two patients reported in the literature with esophagitis dissecans superficialis due to bisphosphonates was a 90-yearold woman who was bedridden and had been taking alendronate while in bed. 20 Esophagitis dissecans superficialis has also been observed in patients with strictures, severe infectious esophagitis, renal failure, and in association with various autoimmune bullous dermatoses, including pemphigus vulgaris and bullous pemphigoid, both of which have cleavage planes that are occasionally seen histologically in esophagitis dissecans superficialis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] Interestingly, one of the two patients reported in the literature with esophagitis dissecans superficialis due to bisphosphonates was a 90-yearold woman who was bedridden and had been taking alendronate while in bed. 20 Esophagitis dissecans superficialis has also been observed in patients with strictures, severe infectious esophagitis, renal failure, and in association with various autoimmune bullous dermatoses, including pemphigus vulgaris and bullous pemphigoid, both of which have cleavage planes that are occasionally seen histologically in esophagitis dissecans superficialis.…”
Section: Discussionmentioning
confidence: 99%
“…13,17 A wide age range with equal sex distribution is reported in the literature, and cases have been reported in healthy young adults, who often present with dysphagia or odynophagia or who rarely may vomit a membranous cast. [13][14][15][16][17][18][19][20][21] Therefore, esophagitis dissecans superficialis shares with sloughing esophagitis the facts that both of them are intraepithelial abnormalities, both may be drug-related, and both may have endoscopic membranes. However, esophagitis dissecans superficialis seems, in some cases, to have associations that are not observed in sloughing esophagitis, and often has different histologic patterns and different clinical presentations.…”
Section: Discussionmentioning
confidence: 99%
“…No particular cause could be identified for the condition but the authors concluded stasis and contact injury due to multiple medications may lead to the condition. Other case reports have described associations with medications, typically bisphosphonates [8] and post sclerotherapy of varices [9]. One of the four patients we describe here was over 60 year's age and one was female.…”
Section: Discussionmentioning
confidence: 59%
“…[2], la dysphagie était le principal signe révélateur. Parfois, on peut avoir une simple dyspepsie ou une odynophagie [4]. Dans nos deux premières observations, la dysphagie était le signe révélateur alors que chez notre dernière patiente la découverte était fortuite.…”
Section: Observation N Ounclassified
“…L'oesophagite disséquante peut être primitive ou secondaire à certaines affections dermatologiques (lichen plan, pemphigus vulgaire, pemphigoïde bulleuse), à des causes traumatiques (syndrome de Mallory-Weiss, sonde nasogastrique), médicamenteuses (biphosphonate) [4], à un reflux gastro-oesophagien ou d'origine infectieuse [2][3][4][5]. De rares cas ont été décrits associés à une insuffisance rénale chronique [6] ou secondaires à une sclérose ou à une ligature de varices oesophagiennes [1].…”
Section: Observation N Ounclassified